(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Pregnancy and childbirth are biological events whose experience is conditioned by the culture and society in which they occur. The purpose of this paper is to highlight the need for a paradigm shift in the surveillance of intrapartum fetal well-being, in order to solve the double Gordian knot, bioethical and medico-legal, which pre-vents in industrialized countries from experiencing those archetypal emotions inherent of the joy that accompanies the birth event. In the conclusions it is suggest-ed that the adoption of informed consent in the delivery rooms and the Daubert criteria in the courtrooms may lead to a resolution of the tense relationships between parturient and doctors and between Science and Justice.